Education Exclusion and Dropping out in Public Schools of Costa Rica - Wendy Jiménez-Asenjo; Marcelo Gaete-Astica (Universidad Nacional, Costa Rica, 2013)
This paper reports on the findings obtained from a study conducted in 2009: "Exclusión educativa y abandono (deserción) escolar en la enseñanza secundaria en Costa Rica" [Education Exclusion and Dropping out in Costa Rica], focused on the students from the 7th to the 11th grades of the General Basic Education. For this research, fieldwork was carried out in 22 institutions, in different educational regions of the country. Interviews were conducted with the school principals and counselors in each of the institutions visited. Focal groups were organized with students and parents in order to -as naturalism and qualitative focus suggest -understand the meaning of education exclusion and dropping out from the point of view of the different agents involved- principals, counselors, students, parents. A relevant conceptual aspect included in this study is the analysis of the problems related to dropping out and exclusion, generally, in a nonjudgmental way, to characterize this phenomenon.